Use of oral rivaroxaban in cerebral venous thrombosis. Issue 1 (15th December 2021) - Maqsood, Muhammad; Imran Hasan Khan, Muhammad; Yameen, Mubashar; Aziz Ahmed, Kashif; Hussain, Nazim; Hussain, Safdar
Abstract: Background: Cerebral venous thrombosis (CVT) is an uncommon cause of stroke in humans and the mainstay of treatment is anticoagulation unless contraindicated. Non-vitamin K oral anticoagulants have not been duly evaluated in randomized controlled trials in CVT. Objective: To compare the efficacy and safety of oral rivaroxaban with vitamin K anticoagulant (warfarin) in preventing recurrent venous thromboembolism (VTE) in patients with CVT. Methods: Adult patients with CVT, who were stable after 5–12 days of treatment with parenteral heparin 1 mg/kg, were screened for eligibility. The patients were randomly divided into two groups to receive oral rivaroxaban 20–30 mg daily or warfarin 1, 3 or 5 mg daily (with the dose adjusted to maintain an INR of 2–3), for 3–12 months. Recanalization rates, periprocedural complications, and clinical outcomes were assessed by Magnetic Resonance Venography (MRV) and National Institutes of Health Stroke Scale (NIHSS) at 3rd, 6th and 12th month follow-ups. Results: In total, 45 patients with CVT were randomized to the two treatment groups (21 to rivaroxaban and 24 to warfarin). Overall recanalization was achieved by 18 (86%) and 20 (83%) cases from rivaroxaban and warfarin group, respectively at 6th month follow-up; and by all 45 (100%) cases from the both groups at 12th month follow-up. Excellent outcome (NIHSS score 0) was obtained by 20 (95%) cases from rivaroxaban group at 3rd to 12th month follow-ups; and by 23 (96%) cases at 6th to 12th month follow-ups. There were no major bleeding events during the trial. None of the patients developed recurrence of thrombosis. Statistically, no significant difference between the two treatment groups in terms of recanalization and clinical outcomes could be observed. Conclusion: Rivaroxaban is a safe option in CVT however; larger randomized controlled studies will impact the results validity.